Visual design for online learning - Davis, Torria 1966- (San Francisco, CA Jossey-Bass, 2015)
"Update the visual design of your course in pedagogically sound ways Visual Design for Online Learning spotlights the role that visual elements play in the online learning environment. Written for both new and experienced instructors, the book guides you in adding pedagogically relevant visual design elements that contribute to effective learning practices. The text builds upon three conceptual frameworks: active learning, multiple intelligences, and universal design for learning. This resource explores critical issues such as copyright, technology tools, and accessibility and includes examples from top Blackboard practitioners which are applicable to any LMS. Ultimately, the author guides you in developing effective visual elements that will support your teaching goals while reinforcing the learning materials you share with your students. There has been a steady increase of over 10% in online enrollment for higher education institutions since 2002, yet the visual look of online courses has not changed significantly in the last ten years. Adapting to the needs of students within online classes is critical to guiding your students toward success--and the right visual elements can play an integral role in your students' ability to learn and retain the information they need to thrive in their chosen programs. In fact, visual elements have been shown to increase student participation, engagement, and success in an online course. Leverage the best practices employed by exemplary Blackboard practitioners Explore three foundational conceptual frameworks: active learning, multiple intelligences, and universal design for learning Increase student retention and success Visual Design for Online Learning is an essential reference for all online educators--both new and experienced"--Provided by publisher.
"Visual elements have been shown to increase student retention, active learning, and contribute to student success in an online course. Instructors need to be able to add pedagogically relevant visual design elements that contribute to student learning, for both new courses and updated or revised courses. With the examples from exemplary Blackboard practitioners, the author has designed a framework that facilitates the use of the pedagogically relevant visual elements, which contributes to overall student retention and success. This book builds on three conceptual frameworks for the design of content --active learning, multiple intelligences, and universal design for learning. The book also explores critical issues such as copyright, technology tools, and accessibility"--Provided by publisher.
Includes bibliographical references (pages 173-176) and index.
Keywords: Internet in education; Instructional systems -- Design; Visual communication